Representasi Wanita Karier dalam Film The Most Beautiful Girl In The World - Pristy Yulia Damayanti; Elpa Hermawan; Ondy Ondy (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
The development of technology and digital platforms such as Netflix has influenced the representation of career women in films, including how career women are depicted in the competitive world of work. This study examines the representation of career women in the film The Most Beautiful Girl In The World, especially through the character of Kiara, a smart, ambitious, and assertive television producer. The purpose of this study is to find out how career women are represented in the film, the values they uphold, and the messages they convey regarding women in the world of work. This study uses a descriptive qualitative approach with Roland Barthes' semiotic analysis method to analyze the denotative, connotative, and mythical meanings in the film. The results of the study show that the character of Kiara represents a modern woman who is independent, professional, and able to compete on an equal footing with men without eliminating her emotional side. This film not only presents women as story sweeteners, but as central figures who bring change to the narrative flow. This representation provides inspiration and motivation for the audience, especially women, in facing stereotypes and challenges in the world of work. This film also conveys an important message about and empowering women in the professional realm.